2006
DOI: 10.1021/la0528100
|View full text |Cite
|
Sign up to set email alerts
|

Transitions of Organized Assemblies in Mixed Systems of Cationic Bolaamphiphile and Anionic Conventional Surfactants

Abstract: The transition from vesicles to tubelike structures has been studied in mixed systems of cationic bolaamphiphile BPHTAB [biphenyl-4,4'-bis(oxyhexamethylenetrimethylammonium bromide)] and its oppositely charged conventional surfactants with transmission electron microscopy (TEM) and dynamic light scattering (DLS). This transition can be attributed to the fact that tube-like structures are more stable aggregates than vesicles because of the special molecular packing in the aggregates of the mixed systems. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Under these assumptions, d of the SDS membrane is estimated as 1.23 nm. And it is reported that the distance from the polar head to the tail end of alkyl chains for SDS monolayer is 1.7 nm [41]. The estimated value of d suggests that, when MWNTs electrode is soaked in SDS solution, SDS molecules can form a monolayer on the surface of MWNTs slantways.…”
Section: à2mentioning
confidence: 95%
“…Under these assumptions, d of the SDS membrane is estimated as 1.23 nm. And it is reported that the distance from the polar head to the tail end of alkyl chains for SDS monolayer is 1.7 nm [41]. The estimated value of d suggests that, when MWNTs electrode is soaked in SDS solution, SDS molecules can form a monolayer on the surface of MWNTs slantways.…”
Section: à2mentioning
confidence: 95%
“…This is based on the observation that bolaamphiphiles are known to form self-aggregating structures that readily convert from vesicles to fibers or sheets upon small changes in their structure,128,151 especially with small vesicles due to curvature considerations 186. Thus, vesicles made from bolaamphiphiles will have superior stability as described above, and yet, upon removal of the head groups, the content of the vesicles will be readily released.…”
Section: Bolaamphiphiles and Nano-structures For Drug Deliverymentioning
confidence: 99%
“…Under this background, researches on the mixed systems of bolas and oppositely charged conventional surfactant systems have attracted increasing attentions [64][65][66][67][68][69][70][71][72][73]. Many interesting novel results have been reported.…”
Section: Introductionmentioning
confidence: 99%